FEKO Simulation of a Wedge Mounted Four Element Array Antenna - Weiss, Steven; Coburn, Keefe; Kilic, Ozlem (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A four element patch array with main beam locations approaching endfire has been developed. The initial design was accomplished using EMAG’s EMPicasso software. The array is intended to be used in a monopulse configuration on the sides of a wedge-like structure. As such, accurate estimations of the patterns need to be obtained when the antenna is mounted on the geometry of the wedge. These simulations were not possible with 2.5 dimensional software, such as EMPicasso (www.emagware.com). We present measured data as compared to simulations using FEKO (www.feko.info) software for the array on a wedge.